Okra ameliorates hyperglycaemia in pre-diabetic and type 2 diabetic patients: A systematic review and meta-analysis of the clinical evidence - Mokgalaboni, Kabelo; Lebelo, Sogolo Lucky; Modjadji, Perpetua; Ghaffary, Saba (Frontiers in Pharmacology, 2023)
Background: Despite the use of available pharmaceutical drugs, high rates of metabolic diseases and cardiovascular disorders are alarming. This calls for alternative therapies that can attenuate these complications. Therefore, we investigated the beneficial effects of okra on glycaemic control in pre-diabetes and type 2 diabetes mellitus (T2D). Methods: MEDLINE and Scopus were searched for relevant studies. Collected data were analysed using RevMan and reported as mean difference and 95% confidence intervals (CI). Eight studies, including 331 patients with pre-diabetes or T2D, were eligible. Results: Our findings showed that okra treatment reduced the levels of fasting blood glucose: mean difference (MD) = -14.63 mg/dL; 95% CI [-25.25, -4.00, p = 0.007]; I2 = 33%, p = 0.17) compared to placebo. Glycated haemoglobin, however, did not differ significantly between the groups: MD = 0.01%; 95%CI [-0.51, 0.54, p = 0.96]; I2 = 23%, p = 0.28). Conclusion: this systematic review and meta-analysis found that okra treatment improves glycaemic control in patients with pre-diabetes or T2D. The findings suggest that okra may be used as a supplemental dietary nutrient, especially in pre-diabetic and T2D patients due to its potential to regulate hyperglycaemia.